Gender, anonymity and team: What determines crowdfunding success on kickstarter - Saif Ullah; Yulin Zhou (Journal of Risk and Financial Management, 2020)
Crowdfunding allows the public to donate small amounts of money to entrepreneurs through online platforms. In contrast with traditional financial institutions, this new method facilitates the financing process through direct and easy online contact between initiators and investors. Based on the data obtained from Kickstarter, the largest crowdfunding platform, we investigate 27,117 crowdfunding projects from 1 January 2015, to 30 June 2015, and we find that a crowdfunding campaign with a realistic funding goal, a suitable funding period, and more updates and interactions with investors is much more likely to be successfully funded. In addition, the different types of founders are very influential in crowdfunding outcomes. For example, females tend to be more successful than males at collecting funds. Founders in the form of teams, companies, or a specific project are also beneficial to funding outcomes.
Keywords: 330; anonymity; crowdfunding; gender; teams